Ten Years of Professional Reinsurance in Nigeria - Irukwu, J. O. (Lagos: Nigeria Reinsurance Corporation, 1977)
This publication is divided into four sections. Section 1 deals with the establishment of the Nigeria Reinsurance Corporation and the main provisions of Decree No. 49 of 1977. Section 2 contains brief profiles of some of the personalities that contributed to the development of reinsurance in Nigeria. Section 3 contains a number of articles and reports by different contributors on Insurance and Reinsurance in the context of recent developments in the national economy. Section 4 contains select views from the industry.
ne 16/05/2018
Loan
Keywords: Reinsurance; Nigeria